(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In current scenario the importance of QUALITY OF WORK LIFE has been increasing. It describes about professional environment and humanistic values that are degraded to some extent. As professionals are unable to balance both their professional and personal life. This variation has made organization to make new policies; it leads to enhance job satisfaction and performance of employee. The level of performance has been referred to QUALITY OF WORK LIFE. It is a method in an organization that helps its members at all level to participate actively and efficiently. This study focuses on performance of employee. The parameters which have been selected to observe the QWL in this study are social factors, economic factors training and development, of the employees. The main objective of this study is to examine the various factors influencing QUALITY OF WORK LIFE at Big Bazaar. The sample size taken for this study is 100 samples the methodology followed for taking sample is questionnaire method in Big Bazaar at Hyderabad. The technique used for this sample is correlation. The variables used in this test are quality of work life is an independent variable and performance of the employee is dependent variable.